2014
DOI: 10.1007/s10973-014-4036-4
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of the complex process of poly(vinyl alcohol) pyrolysis using a new coupled peak deconvolution method

Abstract: A peak deconvolution procedure used for the analysis of data corresponding to simultaneous overlapping processes begins with separation of individual processes using functions such as Gaussian, Lorentzian, Weibull, and Fraser-Suzuki (FS) followed by application of kinetic analysis methods to the separated peaks. We propose a coupled peak deconvolution procedure to link the parameters of the FS functions of similar peaks in two DTG curves obtained at different linear heating rates, so that the coordinates of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The first step is analogous to that recorded in air atmosphere and corresponds to the loss of water molecules (found mass loss 5.25 %). As it has already been mentioned the FTIR [56,57]) appear in the FTIR spectra of the gaseous products at 110°C. With the increasing temperature the intensity of the bands associated with the release of acid grows, but at 150°C the bands characteristic of CO 2 are also observed.…”
Section: Complexes 2-6mentioning
confidence: 75%
“…The first step is analogous to that recorded in air atmosphere and corresponds to the loss of water molecules (found mass loss 5.25 %). As it has already been mentioned the FTIR [56,57]) appear in the FTIR spectra of the gaseous products at 110°C. With the increasing temperature the intensity of the bands associated with the release of acid grows, but at 150°C the bands characteristic of CO 2 are also observed.…”
Section: Complexes 2-6mentioning
confidence: 75%
“…The TG peaks occur at higher temperatures as the degree of hydrolysis decreases. In other words, the weight loss increases with an increase in the content of residual acetate groups . This is due to the elimination of acetic acid, the intramolecular and intermolecular elimination of water, and probably an increase in the extent of scission reactions with the formation of small and more volatile fragments …”
Section: Resultsmentioning
confidence: 99%
“…Figure is the 3D FTIR spectrum of the evolved gases of PVA(80) pyrolysis at different temperature (time), and the characteristic spectrum of all the volatile products produced at 320, 330, and 450°C are also shown in Figure . These points are the temperatures of the peak points of the deconvoulated curves obtained from partitioning of the derivative thermogram (DTG) into three distinct processes using our new coupled peak deconvolution method …”
Section: Resultsmentioning
confidence: 99%
“…Under these circumstances, an interesting alternative for the analysis of complex conversions is a parallel reaction approach, separating the individual processes by derivative TGA (DTG) peak deconvolution [23], followed by the kinetic analysis of the resulting individual curves. Few studies have been reported for biomass pyrolysis kinetic analysis using DTG deconvolution [24][25][26]. In particular, BG, CS, and OPS kinetic analysis using this alternative approach has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%